An interesting new species of Baccharis (Asteraceae: Astereae) from Minas Gerais, Brazil - Deble, Leonardo Paz; Oliveira-Deble, Anabela Silveira de (Balduinia, 2014)
A new species, named Baccharis variabiliflora is described and illustrated and has its taxonomic affinities discussed. The new species is easily seggregate of all species of the genus by its capitula with central staminate flowers, marginal pistillate flowers and between one and other a group of non functional flowers. Baccharis variabiliflora occurs in Central Brazil, seemingly endemic to the wet grasslands and cerrados of Minas Gerais State.